"The force that keeps you going": Enthusiasm in vocational education and training (VET) teachers' work - Sanna Wenström; Satu Uusiautti; Kaarina Määttä (International Journal for Research in Vocational Education and Training (IJRVET), 2018)
Context: Enthusiasm has been noted to increase productivity and quality at work. In teachers' work, this has a connection to student learning and motivation, as well as teaching quality. In the context of Finnish vocational education and training (VET), research on enthusiasm appears especially topical and relevant because of the ongoing wide reform with emphasis on productivity and efficiency. Approach: In this study, Finnish VET teachers' enthusiasm at work was studied qualitatively. Three research questions were set for this study: (1) How do VET teachers describe their enthusiasm?; (2) What factors strengthen their enthusiasm, according to their descriptions?; and (3) What factors weaken their enthusiasm, according to their descriptions? Altogether, 103 teachers who voluntarily participated in the study completed an online questionnaire on enthusiasm. The data were analyzed through qualitative content analysis. Findings: According to the results, the teachers who participated in the study were very interested in their work. They wanted to share how they experienced enthusiasm in their work. Their enthusiasm manifested as their willingness to develop their skills and expertise. It also showed in their dedication, good job performance, and positive feelings about their work. Student encounters, a positive atmosphere, and work interactions were the main sources of enthusiasm. Lack of resources, changes, cuts in the VET budget, and a lousy work atmosphere weakened enthusiasm. Conclusion: The study found that enthusiasm manifested itself in ways that correspond well with the current VET productivity and efficiency goals. Because enthusiasm was strengthened especially when teachers were working with students, it seems important to ensure a supportive work environment for students also after the VET reform. Positive interactions, collegial support, and working together can help teachers to succeed and to maintain enthusiasm in their everyday work. According to the results of this study, supervisors may play a central role in facilitating teacher enthusiasm.
Keywords: 330; VET; Vocational Education and Training; Teacher; Enthusiasm; Work Engagement; Vocational Education